POPULATION STRUCTURE ANALYSIS IN RODENTS (World Bulletin of Public Health, 2024)
The article presents the analysis of population structure in rodents. In the analysis of the population structure, the territorial etiological structure of the population, the density and growth rates of the population, and the genetic structure of the population were evaluated.